2010
DOI: 10.1111/j.1439-0418.2008.01375.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating compatibility among populations of codling moth Cydia pomonella Linnaeus (Lepidoptera: Tortricidae) from different geographic origins

Abstract: The codling moth Cydia pomonella (Linnaeus) (Lepidoptera: Tortricidae) is a serious pest of pome fruit worldwide and the sterile insect technique (SIT) provides an environmentally acceptable approach for its control. As the pest is present in both the southern and northern hemispheres it would be possible for a rearing facility in the northern hemisphere to supply sterile moths to an SIT programme in the southern hemisphere during the northern winter and vice versa. This could greatly improve the economics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…For tsetse flies see Mutika et al (2001, 2013) and for an evaluation of mating compatibility among codling moth, Cydia pomonella (L) populations from different regions of the world see Taret et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…For tsetse flies see Mutika et al (2001, 2013) and for an evaluation of mating compatibility among codling moth, Cydia pomonella (L) populations from different regions of the world see Taret et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…These studies had far-reaching implications for the application of the SIT: no mating barriers were found between populations of the Mediterranean fruit fly from different continents and hemispheres. These mating studies have now been expanded to other insect groups such as Lepidoptera, and a recent study found also no mating barriers between the codling moth, Cydia pomonella L., populations from different continents and hemispheres (Taret et al, 2010). Conversely, distinct mating barriers were found between populations of A. fraterculus originating from Argentina, Peru, and Brazil implying that AW-IPM programmes with an SIT component can only be implemented using strains for rearing and release that originate from the same geographic region.…”
Section: Discussionmentioning
confidence: 99%
“…Although the codling moth has established throughout most of the apple‐producing areas of the world, studies have revealed the absence of mating barriers between codling moths collected from five different continents (Robinson and Proverbs 1973; Bloem et al. 2010; Taret et al. 2010) and a low level of genetic diversity among codling moth populations from different geographical origins (Pashley and Bush 1979; Buès and Toubon 1992; Buès et al.…”
Section: Introductionmentioning
confidence: 99%